2013
DOI: 10.1158/0008-5472.can-12-3058
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Promotion by Intratumoral Plasmacytoid Dendritic Cells Is Reversed by TLR7 Ligand Treatment

Abstract: Plasmacytoid dendritic cells (pDC) are key regulators of antiviral immunity. In previous studies, we reported that pDC-infiltrating human primary breast tumors represent an independent prognostic factor associated with poor outcome. To understand this negative impact of tumor-associated pDC (TApDC), we developed an orthotopic murine mammary tumor model that closely mimics the human pathology, including pDC and regulatory T cell (Treg) infiltration. We showed that TApDC are mostly immature and maintain their ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
129
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(133 citation statements)
references
References 47 publications
3
129
1
Order By: Relevance
“…The major clinical limitations of many TLR agonists are the risk of dose-limiting toxicities associated with their systemic delivery (10-12) and metastasis stimulation (13-15). Furthermore, some previously investigated TLR agonists are restricted to injection directly into tumor tissue (3,(16)(17)(18), an approach that will likely have limited therapeutic value in cancer patients with metastatic disease.TLR5 is unique among TLRs as a potential target for systemic anticancer immunotherapy. Studies have shown that the only known natural TLR5 agonist, flagellin, flagellin-expressing Salmonella bacteria, and a pharmacologically optimized flagellin derivative named entolimod (CBLB502) have antitumor effects in several tumor models (19-23), including mouse models of liver metastases (24-26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The major clinical limitations of many TLR agonists are the risk of dose-limiting toxicities associated with their systemic delivery (10-12) and metastasis stimulation (13-15). Furthermore, some previously investigated TLR agonists are restricted to injection directly into tumor tissue (3,(16)(17)(18), an approach that will likely have limited therapeutic value in cancer patients with metastatic disease.TLR5 is unique among TLRs as a potential target for systemic anticancer immunotherapy. Studies have shown that the only known natural TLR5 agonist, flagellin, flagellin-expressing Salmonella bacteria, and a pharmacologically optimized flagellin derivative named entolimod (CBLB502) have antitumor effects in several tumor models (19-23), including mouse models of liver metastases (24-26).…”
mentioning
confidence: 99%
“…The major clinical limitations of many TLR agonists are the risk of dose-limiting toxicities associated with their systemic delivery (10)(11)(12) and metastasis stimulation (13)(14)(15). Furthermore, some previously investigated TLR agonists are restricted to injection directly into tumor tissue (3,(16)(17)(18), an approach that will likely have limited therapeutic value in cancer patients with metastatic disease.…”
mentioning
confidence: 99%
“…TLR7 stimulation has previously mostly reported to stimulate anticancer immunosurveillance, for instance through direct stimulation of TLRs on antigens presenting cells, leading to their maturation 39,40 . However, in recent years, TLR7 expression by tumor cells has been associated with a pro-tumoral effect in pancreatic adenocarcinoma 25 and in NSCLC 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pDCinfiltrating primary breast tumors represent an independent prognostic factor associated with poor outcome [55]. Investigating these subtypes of microenvironment cells will provide important clues in breast carcinogenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%